ARTICLE TITLE: THE RESILIENCE OF SYNTAX: THE STRATEGIC IMPORTANCE OF GRAMMAR IN MODERN GLOBAL ENGLISH - Khalilov Bakhodir Tolibovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: In the contemporary era of "English as a Lingua Franca" (ELF), a persistent debate exists regarding whether formal grammar remains a necessity or is an obstacle to communicative fluency. This paper argues that grammar is not a static set of rules but a dynamic "sense-making" framework. It asserts that grammatical competence is the primary safeguard against miscommunication, professional marginalization, and linguistic fossilization in a hyper-connected, high-stakes global society.